Screening and Isolation of Polyhydroxyalkanoates (PHA)-Producing Bacteria from Landfill by using Cocoa Pod Husks as Carbon Source - R Wan Abdul Razak, W; J Mohamad Yusuf, N; Abdul-Aziz, A; K Navaratnam, S; Zubir, I; E Rizlan Ross, E (International Journal of Engineering and Technology, 2019)
Polyhydroxyalkanoates (PHA) are bioplastics, produced by various bacteria as food and energy reservoir. PHA is an alternative for synthetic plastic because they are environmentally friendly and can be degraded naturally by microorganisms. One of the important factors for the growth of PHA producing bacteria is an excess of carbon supply. In order to reduce the overall cost of PHA production, a low cost pure substrate, which is cocoa pod husks (CPH) was used as a carbon source. The objectives of this study were to isolate and screen PHA producing bacteria from landfill samples which are leachate and soil, to identify the PHA producing bacteria by using morphological characterization and 16s rDNA gene sequencing and to determine the best percentage of CPH that can be used as a carbon source for PHA producing bacteria. PHA producing bacteria from leachate and soil from landfill in Jeram, Selangor were screened by using Nile Blue A staining method. Two potential PHA producers with the brightest fluorescence under UV light from each samples were isolated and characterized by using morphological and molecular identification. Results of morphological identification shows all bacterial isolates have a rod shape and have a capsule, three bacterial isolates (L4, S3, S5) have an endospore while the remaining does not have endospore (L1). Three out of four were Gram positive bacteria (L4, S3, S5) and the remaining was Gram negative bacteria (L1). These isolates were confirmed of their identity as K. pneumoniae (L1), B. cereus (L4 & S3) and B. toyonensis (S5) using 16s rDNA gene sequencing. Different concentration of CPH, which are 2% (w/v), 5% (w/v), 7% (w/v) and 10% (w/v) were used to study the best percentage of CPH that can be used as carbon source. PHA accumulation was the highest at 7% (w/v) for all bacterial species tested and lowest at 10% (w/v) CPH except for B. toyonensis.Â  Therefore, K. pneumoniae, B. cereus and B. toyonensis which isolated from landfill show the ability to produce PHA and the used of 7% (w/v) cocoa pod husks as carbon source give the highest PHA accumulation.Â